Social support, health and health behaviours of teenage children of parents working abroad - Tabak, Izabela (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The migration of Poles for economic reasons is a significant social problem in the twenty-first century. In discussions on the consequences of parental migration we can identify two dominant trends: the first treats this situation as close or equal to being pathological due to the risk of family breakdown, attachment disorders and of psychological and pedagogical problems in children; in the second, it is assumed that the effects of migration depend on a combination of risk factors and environmental resources. The aim of this study was to analyse both indicators of social support (from family and school), as well as health, life satisfaction and the health and risky behaviours of teenage children of parents working abroad.
Keywords: migration family; social support; health; health behaviours; adolescents